Peran Tata Usaha Membantu Meningkatkan Mutu Pendidikan di MAPN 4 Medan - Amelia, Yuli; Hadijaya, Yusuf (MODELING: Jurnal Program Studi PGMI, 2024)
The head of administration has a very important role in providing services to students in madrasah institutions. One of the administrative roles is the managerial role and the administrator role. Administration must provide good service to the school community. The focus of the research is the role of administration in helping to improve the quality of education at MAPN 4 Medan. This research uses a qualitative approach. This approach involves discussing problems and investigating in depth, including through observation, recording, interviews, and active involvement in the research process. The research subjects in this study were the Head of the Madrasah, TU, and TU Staff. The research location is the place where researchers conduct research to obtain the necessary data. The research was conducted at MAPN 4 Medan Jl. Griya Martubung residential area, Medan City, Postal code 20253. The results of the research show that administrators who play a managerial role must be able to set a good example as a leader, and be able to supervise their subordinates well. Apart from that, as an administrator you must be able to manage various important letters so that they are managed well.